PERKEMBANGAN KAEDAH TULISAN JAWI, ANALISA BEBERAPA KARYA RAJA ALI HAJI KELANA - Abdul Hamid, Faisal@Ahmad Faisal (Journal of Al-Tamaddun, 2007)
Jawi Script as a heritage of Malays is an adapted Arabic alphabet for writing Malay language. In order to meet the pronounciation needs to Malay words, some extra characters are added by Malays to Arabic alphabet. Jawi alphabet has existed for many centuries in Nusantara (the Malay world) since the advent of Islam and has been one of the earliest scripts used for writing Malay since Pasai kingdom and the era of Malacca Sultanate. Jawi script has been widely used by Malay scholars in the past as the medium of writing literary works of various fields especially on religion and literature. Since the method of Jawi spelling was influenced to a great extent by Arabic language, the writings of Malay scholars were not even particular in terms of spelling and vowel. Therefore, this article will discuss the development of Jawi script method based on some samples of Raja Ali Haji Kelana, Malay well known author of the 19th century works. Amongst are Syair Gurindam Dua Belas, Pengetahuan Bahasa and Kitab Bustan al-Katibin.